Epidemiology of preeclampsia - Sánchez, Sixto (2015)
Epidemiological data and clinical evidence support the thesis that pregnancy represents a metabolic challenge for some women, so that a mild subclinical hyperlipidemia becomes clinically detectable. Preeclampsia represents the most frequent medical complication in pregnancy. Maternal and perinatal mortality is high in Peru. Preeclampsia associated factors include primigravity, paternity change, previous preeclampsia or family history of preeclampsia, young or advanced maternal age, increased body mass index, multiple pregnancy, diabetes mellitus, hyperhomocysteinemia, insulin resistance. We review the associated risk factors and protective factors.